Does Stretching Improve Performance?: A Systematic and Critical Review of the Literature - Shrier, I. (Clinical Journal of Sport Medicine, 2004)
Objective: The purpose of this article was to evaluate the clinical and basic science evidence surrounding the hypothesis that stretching improves performance. Data Sources and Selection: MEDLINE and Sport Discus were searched using MeSH and textwords for English-language and French-language articles related to stretching and performance (or performance tests). Additional references were reviewed from the bibliographies and from citation searches on key articles. All articles related to stretching and performance (or performance tests) were reviewed. Main Results: Of the 23 articles examining the effects of an acute bout of stretching, 22 articles suggested that there was no benefit for the outcomes isometric force, isokinetic torque, or jumping height. There was 1 article that suggested improved running economy. Of 4 articles examining running speed, 1 suggested that stretching was beneficial, 1 suggested that it was detrimental, and 2 had equivocal results. Of the 9 studies examining the effects of regular stretching, 7 suggested that it was beneficial, and the 2 showing no effect examined only the performance test of running economy. There were none that suggested that it was detrimental. Conclusions: An acute bout of stretching does not improve force or jump height, and the results for running speed are contradictory. Regular stretching improves force, jump height, and speed, although there is no evidence that it improves running economy.